1997
DOI: 10.1080/07315724.1997.10718684
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report: effects of zinc and micronutrient repletion on growth and neuropsychological function of urban Chinese children.

Abstract: The findings confirm the essentiality of zinc for growth of children, and show, for the first time, the essentiality of zinc for neuropsychological functions of children. In addition, the need for repletion of other potentially limiting nutrients in studies examining the effects of specific nutrients on growth and neuropsychological functions was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 1 publication
0
53
1
2
Order By: Relevance
“…More sensitive techniques such as knee-height measurements might have helped detect any subtle improvement (Himes et al, 1991). Certainly, Penland et al, (1997) reported a significant increase in knee-height after only 10 weeks, in Chinese children aged 6 -9 y of age receiving a daily supplement containing 20 mg Zn plus micronutrients compared to those receiving a daily supplement of 20 mg Zn alone. In rural Malawi where the prevalence of stunting among rural adults is high (Gibson & Huddle, 1998), any growth response is likely to be constrained by a combination of intrauterine growth retardation and inter-generational effects of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…More sensitive techniques such as knee-height measurements might have helped detect any subtle improvement (Himes et al, 1991). Certainly, Penland et al, (1997) reported a significant increase in knee-height after only 10 weeks, in Chinese children aged 6 -9 y of age receiving a daily supplement containing 20 mg Zn plus micronutrients compared to those receiving a daily supplement of 20 mg Zn alone. In rural Malawi where the prevalence of stunting among rural adults is high (Gibson & Huddle, 1998), any growth response is likely to be constrained by a combination of intrauterine growth retardation and inter-generational effects of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The mean duration of supplementation was 90 d (Cavan et al, 1993). In contrast, in China, neurocognitive function was better in children aged 6±9 y supplemented with zinc for 10 weeks, or zinc with other micronutrients, compared with children with micronutrients alone (Penland et al, 1997). In one study of very low birth weight infants in Newfoundland, Canada, psychomotor development in the ®rst year of life was examined and was found to improve with 3 months' zinc supplementation (Friel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of convincing evidence linking zinc deficiency to childhood growth stunting, 32 increased prevalence of common childhood infections such as diarrhea and pneumonia, 33 reduced appetite among children, 34 impaired neurobehavioral function, 35,36 delayed sexual maturation among adolescents, 37 poor pregnancy outcomes including low birth weight, preterm deliveries, maternal delivery complications, 38 and impaired immune function of the neonate, 39 and increased risk of infant mortality among low birth weight infants. 40 Despite these far reaching consequences, much remains to be learned about efficacious methods to prevent zinc deficiency.…”
Section: Zinc Nutritional Statusmentioning
confidence: 99%